Heroes for my daughter - Meltzer, Brad (HarperStudio, 2012)
Collects the stories of fifty-five extraordinary heroes and ideal role models for girls, including Abraham Lincoln, Marie Curie, Rosa Parks, Helen Keller, Anne Frank, Theodore Roosevelt, and the passengers of United Flight 93.